TRANSFORMASI PENGAJARAN NAHWU-SHARAF DALAM ERA APLIKASI MOBILE - Habibah, Habibah (Insya : Journal of Arabic Studies, 2025)
The teaching of Nahwu-Sharaf as an important foundation in understanding classical Islamic texts has undergone significant development along with the advancement of digital technology. This article discusses how the teaching of Nahwu-Sharaf has been transformed through the use of Android/iOS-based mobile applications, both in terms of methods, media, and learner acceptance. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of users and developers of Arabic teaching applications. The results show that the use of applications such as “Nahwu Wadhih”, “Tashrifan”, and “Learning Arabic” provides a significant improvement in understanding the basic concepts of nahwu-sharaf, as well as creating a more interactive and flexible learning environment.